PELATIHAN DAN IMPLEMENTASI PLTS DALAM MENANGGULANGI HAMA BURUNG PENCURI IKAN UNTUK PENINGKATAN PRODUKSI IKAN NILA - I Wayan Jondra; Ni Wayan Mudiarni; I Nyoman Sukarma; I Wayan Raka Ardana; I Nengah Sunaya (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Bird pests and humans thieving  have disturbance the "Mina Yukti" fish cultivator group, in a day the fish can be eaten up to 4 herons, this is known by the presence of fish bones scattered on near of the pond. This problem affect to the food security of this group, especially in this pandemic crisis era. To overcome this problem is to install lighting installations, because the location of the pool is far from the PLN installation, solar panel  is used to supply the lighting consumption. This activity is packaged in the form of training and installation of PLTS and lighting installations. The training is carried out interactively by according to the principles of andragogy, so that the output of theoretical and practical training is to produce competent personnel and the final construction of solar panel and Lighting Installations. The solar panel installed with a capacity of 100WP, the problems of this group can be solved. In the installation of this solar panel  installation does not use an inverter, to increase the efficiency of PLTS. The training activities, construction and installation of PLTS and lighting installations were carried out by 90 people consisting of lecturers, education staff, students and members of the fish cultivator group “Mina Yukti.